2015
DOI: 10.1098/rstb.2013.0279
|View full text |Cite
|
Sign up to set email alerts
|

A holistic view of marine regime shifts

Abstract: Understanding marine regime shifts is important not only for ecology but also for developing marine management that assures the provision of ecosystem services to humanity. While regime shift theory is well developed, there is still no common understanding on drivers, mechanisms and characteristic of abrupt changes in real marine ecosystems. Based on contributions to the present theme issue, we highlight some general issues that need to be overcome for developing a more comprehensive understanding of marine ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(162 citation statements)
references
References 95 publications
3
159
0
Order By: Relevance
“…These scales are comparable to those of climate forcing in the NWA and NEA (22)(23)(24)(29)(30)(31). Thus, these analyses reveal that, contrary to the prevailing assumption (2,16,17), the scales of fishing mortality are equivalent to those of atmosphere-ocean forcing, and could account for a significant portion of the large-scale synchrony that prevails in these cod stocks.…”
Section: Significancementioning
confidence: 76%
See 1 more Smart Citation
“…These scales are comparable to those of climate forcing in the NWA and NEA (22)(23)(24)(29)(30)(31). Thus, these analyses reveal that, contrary to the prevailing assumption (2,16,17), the scales of fishing mortality are equivalent to those of atmosphere-ocean forcing, and could account for a significant portion of the large-scale synchrony that prevails in these cod stocks.…”
Section: Significancementioning
confidence: 76%
“…In a recent comprehensive literature review (12) it was concluded that "it is well understood by marine scientists that climate variability is a strong driver of changes in fish populations and in fisheries." Although we do not dispute the potential importance of climate, the possibility that commercial exploitation could contribute significantly to these variations (13)(14)(15) has been largely dismissed, the assumption being that fishing mortality could not vary coherently at these scales (2,16,17). Other researchers have argued that estimates of exploitation rates often do not exist or are difficult to obtain, thereby limiting the incorporation of such effects into climate-related analyses of fish population dynamics (18).…”
mentioning
confidence: 99%
“…The ecosystem science challenge More and more marine ecosystems provide examples of sudden and dramatic changes or regime shifts (Andersen et al 2008, de Young et al 2008, Conversi et al 2015. Often, regime shifts can be traced back to the interaction of environmental drivers with ecological processes , Thrush et al 2014.…”
Section: Challengesmentioning
confidence: 99%
“…Isolating and quantifying the effects of a single factor remains challenging both because we lack critical data and multiple variables have likely interacted and contributed to alewife dynamics. Moreover, determining the relative importance of top-down or bottom-up effects is fraught with difficulty (Allen 2015), and a more holistic approach has been advocated for investigating the role of exogenous drivers and internal mechanisms in explaining ecosystem change (Conversi et al 2014). He et al (2015) argue that "predation played an important role in the alewife collapse during 2003 in the main basin of Lake Huron and remained important in suppressing their abundance in subsequent years", but their misapplication of the trawl survey data makes this an unsubstantiated conclusion.…”
Section: The Role Of Predation In Prey Fish Population Dynamics and Tmentioning
confidence: 99%